Estudios de literatura peruana. - Cornejo Polar, Jorge
Manual Asencio Segura. Ricardo Palma. César Vallejo. César Atahualpa Rodríguez. Estuardo Núñez. José María Arguedas. Ciro Alegría. Juan Gonzalo Rose. Javier Sologuren. Javier Heraud.